The Relationship Between Economic Growth And The Level Of Community Welfare : Empirical Study In Riau - aswanto aswanto; Emkhad Arif (CV Pena Jaya Pers, 2026)
Economic growth and the level of public welfare are very important and inseparable in a country's development process. This study aims to analyze the relationship between economic growth and the level of public welfare in Riau Province. Public welfare in this study is proxied through the Human Development Index (HDI), which reflects the dimensions of health, education, and income. The data used are secondary data sourced from the Central Statistics Agency (BPS) of Riau Province. The data analysis method in this study uses simple linear regression analysis with the help of the Eviews 13 application. The results of this , study indicate that economic growth has a positive and significant effect on the level of public welfare in Riau Province. Increased economic growth has been proven to be able to encourage improvements in creating public welfare. As proven by the coefficient of determination value of 0.5576 or 55.76%, of course there are many other factors that can also influence the level of public welfare. Therefore, it can be interpreted that economic growth has a positive relationship with the level of welfare. The implications of this research emphasize the importance of formulating regional economic development policies that focus on increasing economic growth and community welfare.